2020
DOI: 10.7196/samj.2020.v110i3.14290
|View full text |Cite
|
Sign up to set email alerts
|

Anal squamous cell carcinoma in KwaZulu-Natal Province, South Africa, with special reference to the influence of HIV infection on clinical presentation and management outcome

Abstract: This open-access article is distributed under Creative Commons licence CC-BY-NC 4.0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Subgroup analysis demonstrated that, even among African patients (who are generally younger overall), HIV positive patients were younger than HIV negative patients. International studies have similarly shown that HIV infected individuals present at a younger age in most cancers such as lung, liver, anal and breast 2,25 and more specifically in CRC [26][27][28] . It is tempting to speculate that this presentation at a young age may be related to accelerated aging seen in HIV-infected individuals 29,30 , or gut flora dynamics in the HIV-positive patient [30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis demonstrated that, even among African patients (who are generally younger overall), HIV positive patients were younger than HIV negative patients. International studies have similarly shown that HIV infected individuals present at a younger age in most cancers such as lung, liver, anal and breast 2,25 and more specifically in CRC [26][27][28] . It is tempting to speculate that this presentation at a young age may be related to accelerated aging seen in HIV-infected individuals 29,30 , or gut flora dynamics in the HIV-positive patient [30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Large series of ASC and their outcomes have been reported in a South African cohort. 73 Obstetric fistula including RVF is most common in certain Middle Eastern and African countries where poor antenatal care and young age at first pregnancy are common. A qualitative study from Iran demonstrated the complex social, individual, and familial issues resulting from this debilitating condition.…”
Section: Colorectal Research In Lmicsmentioning
confidence: 99%
“…A study from South Africa described the management of 268 patients with SCCA. 44 Half the patients were eligible for definitive therapy at the time of diagnosis. Notable within this study was the observation that the proportion of patients who did not receive any treatment at all was higher among HIV-positive patients than among those who were HIV-negative (24 vs 12%).…”
Section: Available Treatment Approaches and Outcomesmentioning
confidence: 99%